Case Report: A case of superficial spreading malignant melanoma with sentinel lymph node metastasis misdiagnosed as “pigmented nevus” - Bu, Xiaolin; Guo, Jing; Feng, Liwei; Liu, Yeqiang (Frontiers in Immunology, 2026)
A 45-year-old woman presented with a black hemispherical plaque on her right lower leg that had developed three years ago without an obvious cause. The lesion gradually enlarged without pain or pruritus. After excision, histopathological examination revealed atypical Spitz nevus. At a dermatology specialty hospital, pathological review suggested superficial spreading melanoma. Immunohistochemistry revealed diffusely positivity for S100, Melan-A, Ki-67, P16, Sox-10 and HMB45. Molecular pathological testing revealed mutations in the TERT promoter and BRAF and CDKN2A/B genes. Extended tumor resection with an intraoperative sentinel lymph node biopsy identified SN2/2. Dissection of the right inguinal lymph nodes revealed melanoma metastasis in 10 of 14 lymph nodes, with Immunolohistochemistry showing diffusely positivity for Sox-10 and Melan-A. The final diagnosis was superficially spreading malignant melanoma with regional lymph node metastasis. Postoperative adjuvant therapy included systemic chemotherapy and targeted therapy. No recurrence was observed during the 2-year follow-up period.